The penalty of imprisonment and its impact on the health of inmates - preliminary results - Józefa Dąbek; Halina Kulik; Rafał Zdrzałek; Karolina Stolorz; Oskar Sierka (Kazimierz Wielki University, 2023)
Introduction and purpose The prison system is an extremely important element of the country's penal structure. Restrictions related to serving a sentence of imprisonment adversely affect the physical health and the mental health of inmates. The main goal of the study was to assess selected areas of health of respondents in prison and changes in them depending on the time spent in prison. Material and methods The study included 153 (100%) men aged 18 to 55 staying in the Penitentiary Institution in Racibórz. An original questionnaire consisting of questions concerning the described issues was used to conduct the study. All respondents provided informed consent to participate. Obtained results in each category were converted into 5-point Likert Scale. Statistical analysis was carried out using the Chi2 test to investigate the relationship between the obtained results and the time spent in prison. Results Almost 30% of respondents declared the presence of chronic diseases before imprisonment, and more than half of the most common ailments after imprisonment included heartburn. Conducted analysis showed that even though more than 60% of the respondents assessed their general health positively there was a significant difference (Chi2=13.8; p=0.0083) between obtained results and inmates' self-assessment. Time spent in prison was not influencing significantly physical health (Chi2=9,9 p=0,624) and inmates' pro-health behaviors (Chi2=18,0 p=0,3232), but it influenced mental health (Chi2=28.3; p=0.047) and lifestyle (Chi2=37.4; p=0.0052). Conclusion The conducted evaluation shows how inmates' health and its determinants are changing during time spent in prison. Moreover, it shows the problems that have to be resolved to maintain health during time spent in prison. It also highlights the importance of taking actions leading to inmates' health improvement.